Resistance of Ahasverus advena and Cryptolestes ferrugineus to Phosphine on Imported Cocoa Beans from Cameroon, Ivory Coast, and Dominican Republic - Franciskus Parasian; Y. Andi Trisyono; Edhi Martono (Jurnal Perlindungan Tanaman Indonesia, 2018)
Ahasverus advena and Cryptolestes ferrugineus were the most frequent pests found on cocoa beans in consignment. Their high infestation could contaminate cocoa beans and put the impact on its quality and economic value. Phosphine is one of the most commonly used fumigant in fumigation treatment to control the pest. The resistance status of A. advena and C. ferrugineus carried by cocoa beans from abroad to Indonesia against phosphine has not been reported. The purpose of this research was to determine the resistance of A. advena and C. ferrugineus to phosphine in the imported cocoa beans. The insects were collected from cocoa beans in consignment from Cameroon, Ivory Coast, Dominican Republic, and storing warehouse in Bandung, Indonesia. C. ferrugineus  from Bogor (SEAMEO BIOTROP) and A. advena  from Cianjur (PT IGE), Indonesia were utilized as the reference populations. Resistance assay was conducted based on Food Agriculture Organization’s standard method. The resistance testing consisted of six phosphine concentrations: 0 (control), 0.005, 0.014, 0.023, 0.031, and 0.040 mg/l for 20 and 48 hours. The resistance classification testing was carried out with concentration 0.25 mg/l for 48 hours. A. advena originating from Cameroon, Ivory Coast, Dominican Republic and Bandung were susceptible to phosphine. C. ferrugineus coming from Cameroon, Ivory Coast (San Pedro and Abidjan) and Bandung were resistant to phosphine, while Dominican Republic’s population remained susceptible to phosphine. C. ferrugineus from Cameroon, Ivory Coast (San Pedro and Abidjan) categorized into strong resistance, while the Bandung population was weakly resistant. IntisariAhasverus advena dan Cryptolestes ferrugineus adalah hama yang sering ditemukan pada biji kakao di dalam petikemas. Infestasi hama ini dalam jumlah yang tinggi bisa mencemari biji kakao dan berdampak pada kualitas dan nilai ekonominya. Fosfin merupakan salah satu fumigan yang sering digunakan dalam perlakuan fumigasi untuk mengendalikan hama tersebut. Status resistensi A. advena dan C. ferrugineus yang terbawa biji kakao dari luar negeri ke Indonesia terhadap fosfin belum dilaporkan. Tujuan penelitian ini adalah untuk menentukan resistensi A. advena dan C. ferrugineus yang terbawa biji kakao impor terhadap fosfin. Serangga uji diambil dari biji kakao di dalam kontainer yang berasal dari Kamerun, Pantai Gading, Republik Dominica, dan gudang penyimpanan di Bandung, Indonesia. C. ferrugineus yang berasal dari Bogor (SEAMEO BIOTROP) dan A. advena dari Cianjur (PT IGE), Indonesia dipergunakan sebagai populasi referensi. Pengujian resistensi berdasarkan metode standar Food Agriculture Organization. Pengujian resistensi terdiri dari 6 (enam) konsentrasi fosfin yaitu 0 (kontrol); 0,005; 0,014; 0,023; 0,031; dan 0,040 mg/l selama 20 dan 48 jam. Pengujian klasifikasi resistensi dengan konsentrasi 0,25 mg/l selama 48 jam. A. advena yang berasal dari Kamerun, Pantai Gading, Republik Dominica dan Bandung rentan terhadap fosfin. C. ferrugineus yang berasal dari Kamerun, Pantai Gading (San Pedro dan Abidjan) dan Bandung resisten terhadap fosfin, sedangkan populasi asal Republik Dominica tetap rentan terhadap fosfin. C. ferrugineus yang berasal dari Kamerun, Pantai Gading (San Pedro dan Abidjan) tergolong resisten yang kuat (strong resistant), sedangkan populasi dari Bandung resisten yang lemah (weak resistant).